Genetic Variation of Hepatic Enzymes Influence on β-Blocker Dose in Patients With Reduced Ejection Fraction Heart Failure. (February 2020) - Ingram, Adam; Valente, Megan
Beta-blockers such as metoprolol, carvedilol, and bisoprolol are indicated for the treatment of patients with reduced ejection fraction heart failure. Heart failure treatment guidelines call for titration of these medications to specific target doses for morbidity and mortality benefit. Hepatic enzymes are responsible for metabolizing these medications; however, these enzymes are subject to genetic variations (polymorphisms) that can increase or decrease enzyme activity. Metoprolol relies almost exclusively on this enzyme for degradation to inactive metabolites, whereas carvedilol relies on this enzyme only partially for metabolism, and the portion of drug that is metabolized by CYP2D6 becomes active metabolites. The clinical significance of genetic variations in CYP2D6 in heart failure patients requiring treatment with carvedilol and metoprolol remains unclear, and further research is needed before any strong recommendations on treatment approach can be made. However, based on what is known regarding the incidence of genetic variations of this enzyme, it is reasonable to conclude that heart failure patients of European and Asian ancestry may be at a greater risk of intolerance to guideline-directed doses of metoprolol. Patients of North African ancestry may be at a lower risk of intolerance to metoprolol, although limited data are available to conclude. Additionally, due to the significant prevalence of CYP2D6 enzyme variations among all ethnicities, it may be reasonable to consider switching to carvedilol for patients who are unable to fully titrate metoprolol.